La lectoescritura para el desarrollo del aprendizaje significativo. - Acurio Calvopiña, Mónica Elizabeth (2018)
The research focuses on establishing how literacy affects the meaningful learning of ninth grade students of Basic Education in the Educational Unit "Mariano Montes"; Within the research, concepts were addressed that allowed characterizing the variables of the problem to be solved through the structure of the theoretical framework. As a general objective of the research it was established to determine the incidence of literacy in the development of meaningful learning in the ninth year students of Basic Education in the Educational Unit "Mariano Montes", reaching a diagnosis of literacy in the students and their causes in the deficient process of it. An inductive - deductive method was used, based on previously established information, to establish the necessary subjects to structure the methodological framework, where the results allowed to conceptualize the facts and phenomena obtained through research, data obtained through a previously structured instrument for the reality of the Educational Unit. After obtaining and analyzing the data, it was concluded that the literacy process is deficient because its bases at the beginning of the teaching process were not reinforced in an adequate manner; On the other hand, teachers do not encourage reading, so this has negative repercussions in the process of meaningful learning, because knowledge is not transmitted properly and the expected results in students' learning are not obtained.